Las novelas de Alberto Vanasco: en la estela del surrealismo - Arce, Rafael (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2014)
The paper proposes a reading of Alberto Vanasco’s novelistic work. It focuses on the tension between the avant-garde procedures and the realistic demands of the novel form. This tension has a historical component: the author’s belonging to a polarized generation between the left-wing political commitment and the need for experimentation. Vanasco’s novels make the contradiction between realism and surrealism and between Borges’s teachings and the novel as a form become fruitful. The proposed reading evidences a continuity that goes from the philosophical examination of temporality to the question of the consciousness of the “other” and of the world.